Holocaust memory reframed : museums and the challenges of representation - Hansen-Glucklich, Jennifer (Rutgers University Press, 2014)
Zakhor : the task of Holocaust remembrance, questions of representation, and the sacred -- An architecture of absence : Daniel Libeskind's Jewish Museum Berlin -- Architectures of redemption and experience : Yad Vashem and the U.S. Holocaust Memorial Museum -- The artful eye : learning to see and perceive otherwise inside museum exhibits -- "We are the last witnesses" : artifact, aura, and authenticity -- Refiguring the sacred : strategies of disfiguration in String, the Memorial to the Deportees, and Menora -- Rituals of remembrance in Jerusalem and Berlin : museum visiting as pilgrimage and performance